Chemical Constituents of the Essential Oil of Invasive Chromolaena odorata leaves in Central Nepal - Thapa, Lal B; Pathak, Seeta; Pal, Khadka Bahadur; Miya, Tayer Mohamad; Darji, Tej Bahadur; Pant, Gunanand; Pant, Ramesh Raj (Journal of Nepal Chemical Society, 2021)
Chromolaena odorata is one of the widely distributed invasive alien plants in the tropical to subtropical regions of Nepal. It has the ability to impact native species in its invaded range by multiple modes such as allelopathy including volatilization. This study aims to identify volatile chemical components in the essential oil of C. odorata. The leaf samples of C. odorata were collected from the Radha Krishna Community Forest, Chitwan district of Nepal. The essential oil from the leaves of C. odorata was extracted and the chemical composition of the oil was analyzed by gas chromatography (GC) and GC–mass spectrometry (GC–MS). A total of 19 chemical components from the oil were identified. The major components identified were linalool (21.64%); β-pinene (9.43%); 1,3-cycloheptadiene (8.92%); β-cubebene (7%); cinnamaldehyde (5.30%) and caryophyllene oxide (4.94%). O-methoxy cinnamaldehyde and isoeugenyl acetate were not listed by previous studies as the components in the essential oils of C. odorata. The components identified by this study have allelopathic effects on native plant species, anti-herbivory properties, and medicinal values. Therefore, this study could be important to understand plant invasiveness and utilization of the plant for the extraction of bioactive compounds may contribute to control and manage the plants in the invaded areas.